HUBUNGAN ANTARA INTENSITAS PENGGUNAAN GAWAI DENGAN PERILAKU PHUBBING PADA MAHASISWA - Septia Anami, Widia; Safitri, Ajeng; Razkia, Dwita; Yuliza, Eva (Nathiqiyyah, 2021)
“HUBUNGAN ANTARA INTENSITAS PENGGUNAAN GAWAI DENGAN PERILAKU PHUBBING PADA MAHASISWA